Implementasi Metode Diskusi Dalam Mengembangkan Kemampuan Kognitif Dan Afektif Dalam Pembelajaran Akidah Akhlak Siswa Madrasah Ibtidaiyah Muhammadiyah Tlogodalem Kertek Wonosobo Tahun 2023/2024 - Zunita Dian Handayani; Moh Sakir; Muhammad Najib Al Adib (Jurnal Mahasiswa Kreatif, 2024)
This study aims to determine the effectiveness of the perpetration of the discussion system in developing cognitive and affective capacities in the literacy of aqidah and akhlak of scholars at the Muhammadiyah Tlogodalem Kertek Wonosobo Elementary School in2023/2024.This study uses a descriptive qualitative system. Research data were collected through party observation, interviews with preceptors and scholars, and document analysis.The results of the study showed that the perpetration of the discussion system was proven to be effective in developing scholars' cognitive and affective capacities. scholars' cognitive capacities increased significantly after sharing in learning with the discussion system. This is substantiated by the increase in pupil learning issues on the cognitive capability test. scholars' affective capacities also increased after sharing in learning with the discussion system. This is substantiated by changes in scholars' stations and geste that are more positive, similar as being more active in literacy, more regardful of other people's opinions, and more tolerant of differences.